Analog beamforming for full-duplex mmWave communication with low-resolution phase shifters - R. López-Valcarce; M. Martínez-Cotelo (IEEE International Conference on Communications (ICC), 2021)
Full-Duplex (FD) communication has been the object of recent attention, particularly in sub-6 GHz bands. By enabling in-band simultaneous transmission and reception, these techniques present great potential in terms of spectral efficiency, latency, and medium access flexibility, and their extension to millimeter wave (mmWave) bands can be expected to benefit similarly. The dense antenna arrays available in mmWave offer a large number of degrees of freedom which could be exploited towards self-interference (SI) mitigation in FD. However, analog beamforming architectures based on practical phase shifters make this task quite challenging due to the lack of amplitude control and finite phase resolution. In this context, we consider a single-stream bidirectional point-to-point mmWave FD link, and develop a new analog beamforming design requiring a single radio frequency chain in each direction, explicitly taking into account such hardware-related constraints. Simulation results show that the proposed scheme significantly outperforms previous methods for practical phase shifter resolution values of a few bits.
Keywords: full-duplex; mmWave; rodin